The Incidence of Knee Pain Complaints in Pedicab Riders in the Kemuning District, Palembang - Oktari, Nendy; Jalalin (Sriwijaya Journal of Medicine, 2020)
Background: Knee pain is a major source of disability, and the most frequently complained of disease in people aged 50years and over, this complaint is often associated with osteoarthritis. Complaints of knee pain in OA patients are stronglyassociated with decreased stability of the knee joint. As the main stabilizer in the knee joint, extensor muscle strengthplays a major role in the pain complaints that occur, so that one of the recommended physiotherapy measures for kneeosteoarthritis patients in reducing pain complaints is to exercise the knee extensor muscle strengthening in the form ofpedaling a bicycle. The pedaling movement is a work activity carried out by pedicab drivers. Therefore, this study wasconducted to determine the incidence of knee pain complaints in pedicab riders in the District of Kemuning, Palembang.Method: This type of research is descriptive with cross sectional study design. The study population was pedicab driverswho operated in the Kemuning District of Palembang. Primary data were collected by conducting interviews todetermine whether there were complaints of pain in the knee and assessed by the KOOS Score and Numeric Rating Scale(NRS), as well as measurements of body weight and height. Results: The results showed that 8 pedicab drivers (17.8%)complained of knee pain and 37 pedicab drivers (82.2%) did not complain of pain in their knees. Conclusion: Theincidence of knee pain complaints among pedicab drivers in the Kemuning sub-district of Palembang is lower than that ofpedicab drivers who do not complain of pain in their knees.